Requirement situations as a starting point for competence-oriented coach education in competitive sports - An explorative mixed-methods study - Annalena Möhrle (Bern Open Publishing, 2023)
Competent coaches are the main goal of coach education (International Council for Coaching Excellence et al., 2013). In order to achieve this goal, coach education in Germany has been further developed in a competence-oriented way in recent years - inspired by corresponding developments in teacher education (e.g. Baumert & Kunter, 2013). For example, the German Olympic Sports Confederation, together with (educational) experts, has developed its own competency model for its coach education (Sygusch et al., 2020). The central starting point of this model - based on the discourse on competencies in educational science - is formed by requirement situations of coaches. They "comprise regularly occurring events with which coaches are confronted and which require them to act. Coping with requirement situations needs competencies that are (supposed to be) acquired in a coach education that is oriented towards requirement situations." (Möhrle et al., in review) However, a systematic overview of requirement situations is not yet available for many educational settings - including coach education (Iller & Wick, 2009). This study addresses this desideratum by answering the question "What are requirement situations of competitive sport coaches?". Method The answer is based on an exploratory mixed-methods design (Creswell & Plano Clark, 2007). In the qualitative phase, n = 12 experts in coach education identified 53 association-specific requirement situations, which were concentrated in deductively derived requirement areas using content analysis (Mayring, 2015). In the quantitative phase, n = 280 competitive sport coaches (judo, soccer, field hockey, skiing, table tennis) assessed the extent to which the requirement situations apply to their everyday coaching work by means of a standardized online survey. Results Fifty-three association-specific requirement situations of coaches (field hockey, athletics = 17; judo = 7; ski = 12) were identified and concentrated in seven requirement areas. The core requirement area is training (39%), clearly ahead of analyzing & assessing, coaching in competition, educating & accompanying, management and interacting(15% to 9% each). Eleven requirement situations apply to competitive sports coaches of all participating associations (Example: The coach trains an athlete/training group. For the next weeks, the improvement of general fitness is on the agenda). Discussion The identified and systemized requirement situations enable conceptual and didactic implications for coach education (e.g., further development of curricula, thematization in teaching-learning situations) as well as empirical implications for coach education research (e. g., test development to assess coach competencies). Furthermore, this study not only initiates the discourse on requirement situations in coach education, but also offers orientation to other sport-related educational settings. References Baumert, J., & Kunter, M. (2013). The COACTIVE Model. In M. Kunter, J. Baumert, W. Blum, U. Klusmann, S. Kraus & M. Neubrand (Eds.), Cognitive Activation in the Mathematics Classroom and Professional Competence of Teachers (pp. 25-48). Springer. Creswell, J. W., & Plano Clark, V. L. (2007). Designing and Conducting Mixed Methods Research. Sage. Iller, C., & Wick, A. (2009). Prüfungen als Evaluation der Kompetenzentwicklung im Studium [Examinations as an evaluation of competence development in higher education]. Das Hochschulwesen, 57(6), 195-201. International Council for Coaching Excellence, Association of Summer Olympic International Federations & Leeds Beckett University. (2013). International sport coaching framework. Version 1.2. Human Kinetics. Mayring, P. (2015). Qualitative content analysis. Theoretical background and procedures. In A. Bikner-Ahsbahs, C. Knipping & N. Presmeg (Eds.), Approaches to Qualitative Research in Mathematics Education. Examples of methodology and methods (pp. 365-380). Springer. Möhrle, A., Liebl, S., & Sygusch, R. (in review). Anforderungssituationen als Ausgangspunkt einer kompetenzorientierten Trainer:innenbildung im Leistungssport - Eine explorative Mixed-Methods-Studie[Requirement Situations as a Starting Point for Competence-Oriented Coach Education in Competitive Sports - An Explorative Mixed-Methods Study]. Sygusch, R., Muche, M., Liebl, S., Fabinski, W., & Schwind-Gick, G. (2020). Das Kompetenzmodell für die Trainerbildung: Teil 1 [The competency model for coach education: Part 1]. Leistungssport, 50(1), 41-47.